O009 The Good Sleeper Scale-13 Items: a standardised questionnaire for the assessment of good sleepers. (7th October 2021) - Manners, J; Appleton, S; Reynolds, A; Melaku, Y; Gill, T; Micic, G; Lovato, N; Sweetman, A; Bickley, K; Adams, R; Lack, L; Scott, H
Abstract: Introduction: Good sleep is not merely the absence of sleep disorder symptoms, yet this criterion is commonly applied in research studies. We developed the Good Sleeper Scale-13 (GSS-13) to standardise identification of good sleepers. Methods: We conducted a secondary analysis of the 2019 Sleep Health Foundation online survey of adult Australians (N = 2, 044, aged 18–90 years). Possible GSS-13 items were chosen collaboratively with co-authors. Exploratory factor analysis (EFA) was conducted on 10% of the dataset chosen at random (N = 191) for factor identification and item reduction. Confirmatory factor analysis (CFA) on the remaining 90% (N = 1, 853) tested model fit. Associations with sleep concerns, health, and daytime functioning tested validity of the final version. Results: From EFA, six factors were identified: Adequate Sleep; Insomnia; Regularity; Timing; Sleep Duration; Perceived Sleep Problem. On CFA, model fit was comparable to other sleep instruments, X² (67) = 387.34, p < .001, CFI = .95, TLI = .92, RMSEA = .05. Cronbach's alpha was largely acceptable (≥.7) across subscales. Consistent correlations were found between GSS-13 global scores and outcomes, including "a good night's sleep" (r = .65, p < .001), feeling un-refreshed (r = -.53, p < .001), and general health rating (r = .44, p < .001). Classification accuracy for insomnia symptoms was also high (AUC = .84). Conclusions: The GSS-13 is psychometrically sound, correlated well with sleep, health, and daytime functioning, and can be used to identify good sleepers for research. Future work will test relationships with other sleep measures.